The Silence of Othered Species: The Anthropocene Age, Trauma, and the Ontological Rift - LaMothe, Ryan (Pastoral psychology, 2023)
This article considers the notion of trauma in relation to more-than-human species and in the context of the environmental catastrophes of the Anthropocene Age. The claim is that other species have long experienced suffering and trauma at the hands of human beings and that this will only increase as the effects of climate change worsen. The argument begins by briefly exploring the meanings of trauma before applying this concept to other-than-human species. From here it is argued that the Abrahamic scriptures, along with Western political philosophies and theologies, have served as apparatuses for producing and maintaining an ontological rift between human beings and other species. This ontological rift leads to the exclusion of other species from political questions of human dwelling, which, in turn, provides the "ethical" legitimation of the instrumental and callous exploitation of other species for human desires and needs, resulting in their suffering and trauma. In concluding, the notion of inoperative pastoral care is discussed as a counter to the ontological rift, inviting more empathic, compassionate, and inclusive relations with more-than-human species.